Association of Changes in Thickness of Limbal Epithelial and Stroma with Corneal Scars Detected by High-Resolution Anterior Segment Optic Coherence Tomography - Guclu, Hande; Sattarpanah, Samira; Gurlu, Vuslat (Klinische Monatsblatter fur Augenheilkunde, 2024)
To investigate the corneal central and limbal thickness in cornea scar patients using high-resolution anterior segment optical coherence tomography (AS-OCT) and to determine the changes in the limbal region due to the corneal scar. Also, to evaluate tear film parameters in scar patients. Thirty patients with central corneal scar and 30 control subjects. The control subjects were healthy individuals who came to our clinic for routine ophthalmological examination. They were enrolled in this matched case-control study. Central epithelial thickness (ET), stromal thickness (ST), limbal epithelial thickness (LET), and limbal stromal thickness (LST) were analyzed using high-resolution AS-OCT. For evaluation of the ocular surface, the following techniques were used: tear break-up time (BUT) employing standard sterile strips of fluorescein sodium, Schirmer test-I (SCH), and the Ocular Surface Disease Index (OSDI) Questionnaire. The mean central ET of the patient group was 51.5 ± 12.4 µm, while the mean central ET of the control group was 59.2 ± 9.0 µm. There was a statistically significant difference between patients and controls (p = 0.008). The mean LST of the patients was 747.9 ± 115.7 µm, and the mean LST of the controls was 726.3 ± 79.7 µm. There was a statistically significant difference between patients and controls according to BUT (p = 0.009) and SCH (p = 0.04). However, there was no significant difference between OSDI results of patients and controls (p = 0.08). Corneal monitoring with high-resolution AS-OCT is a simple, noninvasive, useful technique for corneal scar patients. Cornea scars cause decreased ET. This result could be associated with lower tear film parameters in scar patients. The scar length is associated with higher intraocular pressure (IOP) values. Decreased LET and increased LST were detected in scar patients.